Telomerase and non-Telomerase Mechanisms of Telomere Maintenance - Morrish, Tammy A. (IntechOpen, 2020)
This book, Telomerase and non-Telomerase Mechanisms of Telomere Maintenance, is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of biochemistry, genetics, and molecular biology. The book comprises single chapters authored by various researchers and edited by an expert active in the molecular biology research area. All chapters are individually complete but united under a common research topic. This publication aims to provide a thorough overview of the latest research efforts by international authors on biochemistry, genetics,and molecular biology, and open new possible research paths for further novel developments. A note from the publisher: It is with great sadness and regret that we inform the contributing authors and readers of this book that the Editor, Dr Tammy A. Morrish, passed away during the publishing process of the book and before having a chance to see its publication. The book Telomerase and non-Telomerase Mechanisms of Telomere Maintenance was her first edited volume with us. Fruitful collaboration continued until her final days. We would like to acknowledge Dr Morrish's contribution to scientific publishing, which she made during years of dedicated work, and express our gratitude for her pleasant cooperation with us.